Virtual Reality Reduces Pediatric Anxiety During Food Allergy Clinical Trials: A Pilot Randomized, Pragmatic Study - Alonzi, Sarah; Caruso, Thomas J.; Sindher, Sayantani B.; Cao, Shu; Varadharajulu, Sara; Collins, William J.; Chinthrajah, R. Sharon (Frontiers in Allergy, 2022)
Phlebotomy procedures required in food allergy (FA) diagnosis and clinical trials often induce fear and anxiety for pediatric patients. The primary aim of this study was to determine whether virtual reality (VR) applications were effective in reducing anxiety for pediatric FA patients undergoing phlebotomy during FA clinical trials. Secondary aims assessed fear, pain, procedural compliance, and adverse events. Participants undergoing phlebotomy were enrolled and randomized to a VR group or standard of care (SOC) group for this prospective pilot randomized, pragmatic study. Participants in the VR group played interactive applications on a customized Samsung Gear VR headset and those in the SOC group received the standard of care. Participants’ anxiety, fear, and pain were assessed with the Children’s Anxiety Meter, Children’s Fear Scale, and FACES pain scale pre, during, and post phlebotomy procedure. Compliance was assessed using the modified Induction Compliance Checklist during the procedure and compared between two groups. Forty-nine participants were randomized to VR (n=26) and SOC (n=23) groups. Although both the VR and SOC groups experienced a decrease in anxiety and fear from pre- to post-procedure, those in the VR group experienced less anxiety and fear during the procedure than SOC participants. Similarly, both groups experienced an increase in pain from pre- to post-procedure; however, the VR group reported less pain during the procedure than SOC. Fewer symptoms of procedural non-compliance were reported in the VR group. Interactive VR applications may be an effective tool for reducing fear, anxiety, and pain during phlebotomy for FA clinical trials.